UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) DALAM ERA OTONOMI DAERAH - Ratnawati, Tri (Program Doktor Ilmu Ekonomi, 2009)
The Action of Local Original Income growth is the growth of local tax and local retribution with some step is optimalization tariff system, growth of tariff, development the object of tax. Local original income can growthed by local asset management with some step is local asset revitalization with exploration local asset potential through value for money added, by local asset management give effect. Multipleer to growth of local original income, the development of SIMBADA, optimalization BUMD and BUMS contribution, optimalization activity of corporate social responsibility. Keywords : Local original income, optimalization contribution BUMD and BUMS, asset management